Giorgio Caproni. Bibliografia delle opere e della critica (1933-2020) - Baldini, Michela (Moderna/Comparata, 2021)
On the thirtieth anniversary of the death of Giorgio Caproni (Livorno 1912 - Roma 1990), this volume, through the expertise and work of Michela Baldini, proposes a very useful and necessary tool: a complete bibliography of/on Giorgio Caproni, from 1933 to 2020, with almost 4000 reports. The Antologia della critica concludes the volume, offering important studies on Caproni (Betocchi, Bo, Macrí, Dolfi, Ramat, Surdich, Zuliani).